Every Challenge is an Opportunity: Teaching Reading in the Post-Pandemic Period - David, Maya Khemlani; Ali, Ameer (Unisia, 2022)
Drastic changes in the wake of COVID-19 have been witnessed in many sectors. The education sector has also been affected due to lockdowns. Exclusive online teaching methodologies were used due to the closing of schools. Platforms such as Zoom, Eventbrite, Microsoft Teams and many others were used for language teaching. Language teachers were trained regarding the use of digital tools, and this led to a radical shift to online language teaching. However, we are now moving back from enforced online teaching during the initial era of Covid-19 to teacher fronted classrooms. In this research, the focus will be what language teachers have learnt from that time and are using now for more effective teaching of reading skills. Data collected through interviews with 15 teachers and 10 students who have recently shifted to a hybrid way of language teaching and learning were qualitatively analyzed to demonstrate the benefits of hybrid language teaching and learning. Findings show that this methodology is becoming popular among teachers and students, because it enhances both teaching and learning and is effective in achieving teaching and learning goals. In summary, the wise and selective use of digital tools and face to face teaching for the teaching of a range of reading skills improves learning and their strategic use by the teacher should be encouraged and is discussed in this research.